1982
DOI: 10.1007/bf00283741
|View full text |Cite
|
Sign up to set email alerts
|

The diabetic leg

Abstract: Summary. Many clinical problems arise as a result of tissue pathology in the diabetic leg. Neuropathic or vascular ischaemic syndromes are readily identified but on occasions differentiation of the two may be difficult. This survey reviews the aetiological background of neuropathy and ischaemia, examines the relationship of physiological blood flow abnormalities to both areas and comments on management of the clinical states encountered, including the common problem of the ulcerated diabetic foot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

1983
1983
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(41 citation statements)
references
References 38 publications
1
39
0
1
Order By: Relevance
“…Abnormalities of blood flow [6] and venous oxygenation [7] have been reported in the foot with diabetic neuropathy and arteriovenous shunting [8] could partly explain these findings. While our patients had no clinical evidence of significant peripheral vascular disease or neuropathy, early changes in blood flow or nerve conduction could still be present.…”
Section: Discussionmentioning
confidence: 94%
“…Abnormalities of blood flow [6] and venous oxygenation [7] have been reported in the foot with diabetic neuropathy and arteriovenous shunting [8] could partly explain these findings. While our patients had no clinical evidence of significant peripheral vascular disease or neuropathy, early changes in blood flow or nerve conduction could still be present.…”
Section: Discussionmentioning
confidence: 94%
“…This increase is now thought to be due to the dilation of denervated arteriovenous shunts [2][3][4][5][6][7][8][9] normally controlled by sympathetic nerves.…”
Section: Discussionmentioning
confidence: 99%
“…This hypoth esis, known as the capillary steal phenomenon, explains the simultaneous existence of an increased peripheral skin blood flow and trophic skin lesions [4]. Yet Flynn et al found no difference in nutritive blood flow in the toe between patients with and without diabetic neuropathy [5].…”
Section: Introductionmentioning
confidence: 99%